A novel composite edible film fabricated by incorporating W/O/W emulsion into a chitosan film to improve the protection of fresh fish meat. (15th August 2022) - Yuan, Dongdong; Hao, Xu; Liu, Guorong; Yue, Ying; Duan, Jiaojiao
Highlights: An edible chitosan film incorporating double emulsion was developed. Incorporation of W/O/W emulsion increased the chitosan film's oxygen permeability. Film's tension strength was increased by adding W/O/W emulsion at low concentration. The composite film significantly increased the shelf life of salmon fillet. Abstract: A novel edible composite film constructed by incorporating W1 /O/W2 emulsion (W1 : aqueous solution of nisin; W2 : water; oil phase: carvacrol) into chitosan film was characterized. Influences of preparing parameters on properties, especially stability, of primary and double emulsions were evaluated, and more persistent antibacterial activity was achieved. The film's tension strength was increased by incorporating double emulsion at low concentration, but its oxygen permeability increased after this incorporation. The composite film displayed significant inhibitory effects on both Gram-positive and Gram-negative bacteria. SEM showed a sign of aggregation of some emulsion droplets near the surface of the composite film. FTIR found no pronounced interaction between the added active agents and chitosan. TGA proved that the double emulsion helped to increase the thermal stability of the film at high temperature. Coating salmon fillets with the composite film significantly increased the shelf life of fish fillets, demonstrating optimal potency in preserving fish fillets.